Crescimento de mudas de Schizolobium amazonicum (Huber ex Ducke) em substrato fertilizado com nitrogênio, fósforo e potássio - Caione, Gustavo [UNESP]; Lange, Anderson; Schoninger, Evandro Luiz (My University, 2012)
The nutritional management of seedlings in the nursery is one of the most important practices that influence seedling quality. The aim of this work was to evaluate the effect of nitrogen, phosphorus and potassium on the development of Schizolobium amazonicum seedlings grown in 250 cm containers with a commercial substrate in the North of Mato Grosso State, Brazil. The experimental design was completely randomized design with five treatments and five replications, each replication being represented by 24 seedlings. The treatments were: control (only commercial substrate); nitrogen fertilization (150 g m-3 N using ammonium sulfate + 1.0 kg of ammonium sulfate dissolved in 100 L of water and applied in coverage); phosphorus fertilization (300 g P2O 5 m-3 using simple superphosphate); potassium fertilization (100 g m-3 K2O using potassium chloride + 0.3 kg of potassium chloride dissolved in 100 L of water and applied in coverage) and; complete (a mixture of the three nutrients, 150, 300 and 100 g m-3 N, P2O5 and K2O, respectively + 1.0 kg of ammonium sulfate + 0.3 kg of potassium chloride). The commercial substrate was composted milled pine bark plus vermiculite. Evaluations of the seedlings were performed at 90 days after sowing. The complete treatment (NPK) gave the highest values for biometric and best plant indices, which express the quality. When analyzing nutrients in isolation; potassium had the lowest effect. Based on these results it can be recommended to fertilize Schizolobium amazonicum seedlings in nurseries with 150, 300 and 100 g m-3 of N, P2O5 and K2O, respectively, plus 1.0 kg of sulfate ammonium and 0.3 kg of potassium chloride applied in coverage.
Growth of seedlings Schizolobium amazonicum (Huber ex Ducke) on substrate fertilized with nitrogen, phosphorus and potassium
Keywords: Forest species; Native Amazon species; Plant nutrition; Seedling quality; Ammonium Sulfate; Commercial substrates; Completely randomized designs; Mato Grosso; Nitrogen fertilization; Pine bark; Potassium chloride; Potassium fertilization; Ammonium compounds; Biometrics; Chlorine compounds; Clay minerals; Forestry; Nitrogen; Nutrients; Phosphorus; Substrates; Potassium